2011
DOI: 10.1177/1476718x11415578
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding preschool children’s problem solving: A comparison between Chinese mothers and teachers across multiple tasks

Abstract: This study compared Chinese mothers' and teachers' scaffolding of preschool children in different problem solving tasks. Participants were 57 children (including 29 girls) from seven kindergartens in Beijing, their mothers and teachers. Mothers varied in educational levels while all teachers were professionally qualified. Children solved four problems (supermarket, jigsaw puzzle, worksheet, and map) with their mothers and four comparable ones with their teachers. These tasks were appropriate for Chinese five-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
3
20
0
1
Order By: Relevance
“…By privatizing the region’s kindergartens, the Hong Kong government hoped to gain the autonomy to make its own pedagogical decisions in response to parental expectations and market demand, and thereby to upscale the quality of kindergarten education (Fung and Lam, 2009). As discussed earlier, the findings of this study have vividly revealed the persistence of the traditional Chinese emphasis on children’s academic success (Chao, 1994; Mok et al, 2008; Sun and Rao, 2012). Parents’ preoccupation with their children’s academic achievement may problematize the current education-voucher system, which intentionally enhances parental influence on the school curriculum and pedagogy.…”
Section: Discussionsupporting
confidence: 59%
“…By privatizing the region’s kindergartens, the Hong Kong government hoped to gain the autonomy to make its own pedagogical decisions in response to parental expectations and market demand, and thereby to upscale the quality of kindergarten education (Fung and Lam, 2009). As discussed earlier, the findings of this study have vividly revealed the persistence of the traditional Chinese emphasis on children’s academic success (Chao, 1994; Mok et al, 2008; Sun and Rao, 2012). Parents’ preoccupation with their children’s academic achievement may problematize the current education-voucher system, which intentionally enhances parental influence on the school curriculum and pedagogy.…”
Section: Discussionsupporting
confidence: 59%
“…Given the limitations of both observational and survey-based research on parent-child math engagement, there is a need for research that manipulates activity context, but only a few studies have examined contextual effects on parent-child math engagement. Sun and Rao (2012) compared mothers' scaffolding of preschoolers during playful and school-like contexts; however, the contexts utilized two activities-a jigsaw puzzle and arithmetic worksheet-that differed substantially in math content, making it difficult to directly compare the quality and quantity of parent math talk across contexts. To our knowledge only one study has compared two different activities designed to tap into the same math concept.…”
Section: Comparing Contextsmentioning
confidence: 99%
“…The concept of scaffolding is prevalent in many analyses of and discussions about early childhood education and children's learning and development (e.g., Sun & Rao, 2012;van de Pol & Elbers, 2013). Conceptualizing interaction in terms of changing division of labor has proven illuminating of strategies employed in supporting new insights and abilities in children.…”
Section: A Note On Scaffolding and Triggeringmentioning
confidence: 99%